Beta2-microglobulin as a diagnostic marker in cerebrospinal fluid: a follow-up study - Svatoňová, Jana; Bořecká, Klára; Adam, Pavel; Lánská, Věra (Disease markers, 2014)
Beta2-Microglobulin ( β 2-m) is a low molecular weight protein occurring in all body fluids. Its concentration increases in various pathologies. Increased values in cerebrospinal fluid (CSF) are ascribed to an activation of immune system. Using immunoturbidimetry, we examined concentrations of beta2-microglobulin in cerebrospinal fluid in a large group of 6274 patients with defined neurological diseases. Cell counts, total protein, albumin, glucose, lactic acid, immunoglobulins concentrations, and isofocusing (IEF) were also evaluated. We found substantial changes of CSF β 2-m concentrations in purulent meningitis, leptomeningeal metastasis, viral meningitis/encephalitis, and neuroborreliosis, while in multiple sclerosis these changes were not significant. Intrathecal synthesis and immune activation were present in these clinical entities. A new normative study enables better understanding of beta2-microglobulin behavior in CSF.
Keywords: beta-2-mikroglobulin; Young Adult; infekce bakteriemi rodu Borrelia; biologické markery; Child, Preschool; meningitida bakteriální; Meningeal Neoplasms; mladý dospělý; Biomarkers; Multiple Sclerosis; Adolescent; Child; dítě; Adult; meningeální nádory; Aged; dospělí; Borrelia Infections; Case-Control Studies; senioři; mladiství; předškolní dítě; senioři nad 80 let; lidé; studie případů a kontrol; Humans; Aged, 80 and over; beta 2-Microglobulin; Meningitis, Viral; meningitida virová; Meningitis, Bacterial; lidé středního věku; roztroušená skleróza; Middle Aged